(untitled) (International Journal of Ayurveda and Pharma Research, 2020)
Although man has developed sophisticated machines, medical equipment and potent medicines, in spite of all these upgrade, he is lacking proper health. In a quest to achieve more of worldly pleasures and luxury, people are adopting a faulty lifestyle and the disease-causing risk factors and stress in their life are on increase mode. This is the fundamental reason being surge of lifestyle disorders these days. Where obesity is main and root cause of many other lifestyle disorder. A detail description of obesity by name of Sthaulya found in Ayurvedic literature but the material is Scatter and different opinion by different Acharya were there. Ayurveda manage the disorder in a holistic approach with Diet, Lifestyle, medication and Sodhanakarma. So, in present study detail review of Sthaulya with the aim to enlighten the different treatment approaches for the management of Sthaulya (Obesity).